Analysis Of Website Quality Of The Integrated Online Service System (Sipinter) In Situbondo Regency Using The Webqual 4.0 Method - Khairatul Fatati; Ismail Nurdin; Udaya Madjid (CV. AFDIFAL MAJU BERKAH, 2026)
The implementation of electronic government represents a strategic effort by local governments to improve the quality of public services. One such implementation in Situbondo Regency is the Integrated Online Service System (SIPINTER), which functions as a web-based platform for non-business licensing services. SIPINTER is expected to facilitate access to services while supporting transparency and efficiency in the licensing process.This study aims to analyze the quality of the SIPINTER website based on user perceptions using the Webqual 4.0 method, which includes the dimensions of usability, information quality, and service interaction quality. The research adopts a descriptive quantitative approach, with data collected through structured questionnaires distributed to SIPINTER users. Data analysis is conducted using descriptive statistics to describe the quality of the website across each dimension.The results indicate that the quality of the SIPINTER website is perceived as good across all measured dimensions. The website is relatively easy to use, the information provided is considered relevant to user needs, and users demonstrate a satisfactory level of trust in the system as an official government service, despite certain technical limitations. Overall, the SIPINTER website is perceived as highly qualified across the three Webqual 4.0 dimensions based on users’ perceptions, although certain aspects still require improvement. This finding indicates that although the quality of the SIPINTER website is perceived as very good by users, the overall success of licensing services is not determined solely by the quality of the digital platform. The high rate of application rejections is more likely influenced by administrative factors, such as incomplete documentation or non-compliance with required procedures, rather than by the technical aspects of the website itself.